Further Reflections on Moral Education: A Response to Strike - Garlikov, Rick (Education Policy Analysis Archives, 1993)
While moral discourse is in need of much help, there is a solution which is not dependent on Kenneth Strike's remedy of understanding or building character, as such, and which teaches moral reasoning without promoting particular moral values or character traits. Further, contrary to Strike's claim, moral skepticism is not the main problem with moral debate today, which often features diametrically opposed, absolutely certain, dogmatic assertions by all sides. The author teaches ethics courses, and has found among students from a variety of ages and socio-economic backgrounds that the understanding of certain topics in ethics is necessary and often sufficient for promoting more reflective and responsible behavior, and for promoting discourse that has a greater chance to resolve differences.